A STUDY OF IMPACT OF COVID-19 ON IT INDUSTRY IN INDIA - Tejinder Singh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Industries with non-manufacturing nature of business models are realizing that work from home is a new normal whether it is education industry, KPO or BPO services. It is high time that in order to meet the shortfall in revenues for software companies from contraction in exports figures, domestic consumers of software products should prefer Indian companies and not their foreign counterparts. Since majority of IT companies have the ability to rely on digital platforms to ensure continuity in business operations even during the lockdown period, the relative impact on IT sector has been less in terms of operational costs.